Conjugation of Bioactive Molecules to a Fluorescent Dithiomaleimide by Photoinduced and BEt3‐Initiated Thio‐Click Reactions (Eur. J. Org. Chem. 35/2015). Issue 35 (December 2015) - Lázár, László; Nagy, Miklós; Borbás, Anikó; Herczegh, Pál; Zsuga, Miklós; Kéki, Sándor
Abstract : The cover picture shows the coupling of a fluorescent dithiomaleimide bearing a vinyl ether functionality to bioactive compounds through free‐radical hydrothiolation. Out of the photoinduced and triethylborane‐initiated methods applied, the latter was found to be superior for modification of the sensitive maleimide group. All addition products exhibited strong green fluorescence having almost identical absorption and emission spectra, proving that the thiol part has little influence on the fluorescent properties of the conjugates. Details are discussed in the article by S. Kéki et al. on7675 ff .